Letter (copy) : Señor Santiago Gallut Calvo - Max Winter Limited; Tewson, Vincent
1940-01-10 038-0051-001 International HVT/AC/84 10th January, 1940. Mr. E.D. Hunt, Spanish Youth Committee, 15 Great James Street, W.C.1. Dear Sir, Señor SANTIAGO GALLUT CALVO. I have your letter of 8th January, in which you enclose a letter which your Committee has received from Mr. F. Winter and a letter which the latter had received from Señor Gallut. Señor Gallut has written to us himself, asking us, too, to approach the French Minister of the Interior on his behalf, with a view to the extension of his permit to remain in the country. For your information, we have taken the action open to us in this question. Yours faithfully, Assistant Secretary. 292/946/38/51(I)